Transcriptional activation of human papillomavirus 16 by nuclear factor I, AP1, steroid receptors and a possibly novel transcription factor, PVF: a model for the composition of genital papillomavirus enhancers. - Chong, T (1990)
Human papillomavirus 16 (HPV-16), which is involved in genital carcinogenesis, contains an enhancer of transcription that is activated by cellular factors rather than by the viral E2 proteins. The activity resides on a 232 bp segment with 5 binding sites for nuclear factor 1 (NF1), 2 for AP1, and 1 for steroid receptors. Deletions and point mutations show that the constitutive enhancer and the steroid response depend on NF1 sites located 5' or 3' of a 65 bp fragment with AP1 sites that by itself shows little activity. Enhancement through a fragment with AP1 and NF1 sites is strongly reduced by mutation of the AP1 sites, or by mutation of the sequence AGGCACATAT. Sequence comparison and footprint analysis make it likely that this sequence binds a novel transcription factor which we call PVF. Fragments with one or several binding sites only for NF1, or AP1, or PVF exhibit little enhancement by themselves, suggesting the functional dependence of the HPV-16 enhancer on the cooperation of these factors. A comparison of our findings with the genomes and transcription factor binding sites of HPV-6, 11, 18, 31 and 33 lead us to propose a model of the composition of enhancers of genital papillomaviruses.